Edible Bird’s Nest: Recent Updates and Industry Insights Based On Laboratory Findings - Chok, Kian Chung; Ng, Ming Guan; Ng, Khuen Yen; Koh, Rhun Yian; Tiong, Yee Lian; Chye, Soi Moi (Frontiers in Pharmacology, 2021)
Edible bird’s nest (EBN) is a traditional Chinese delicacy made of the saliva of swiftlets found in Southeast Asia. With increasing demands for EBN, quality control of EBN products is important for safe consumption. The processing steps are particularly important for efficient extraction of bioactive compounds. Geographical location, collection place, and harvesting season contribute to differences in nutritional contents in EBN. Concerns regarding presence of adulterant, chemical, and microbial contaminants in EBN as well as authentication and chemical composition measuring methods are discussed in this review. Recent discoveries of beneficial health functions of EBN in antimicrobial and antiviral actions, immunomodulation, cancer prevention and treatment, tissue regeneration, cardiometabolic maintenance, antioxidant action and neuroprotection are also reviewed. Our review provides an update on the recent research on EBN.